(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Viral hepatitis is an inflammatory disease of the liver caused by specific viruses. These viruses can be classified into five main types: A, B, C, D and E. Therefore, the objective was to describe the main characteristics of deaths from viral hepatitis in Brazil in the year 2021. Methods: This is an observational, cross-sectional and descriptive study, with a quantitative approach and using secondary data, through DATASUS, from the SIM. Results: The data provided present information on the characteristics of deaths from viral hepatitis in Brazil, including age range, sex, color/race, education and marital status of people who died due to this disease, number of deaths from viral hepatitis in each region of Brazil and number of deaths from viral hepatitis in Brazil, grouped by type of hepatitis. Discussion: In the year 2021 were notified to the Mortality Information System of Brazil 1,712 deaths by viral hepatitis. As for the characteristics of these deaths, the variables with the highest incidence can be defined as: age 60 to 79 years (823 deaths), male gender (1,078 deaths), white race (865 deaths), education from 8 to 11 years (450 deaths), married (580), southern region and chronic viral hepatitis. Conclusion: Given the relevance to this issue, early diagnosis, treatment and popular education in health is of fundamental importance, aiming at strategies to reduce morbidity, mortality and survival of its carriers.